THE IMPORTANCE OF RUMEN ANAEROBIC FUNGI ON FIBER DEGRADATION IN RUMINANTS: REVIEW - Sinta Agustina; I Komang Gede Wiryawan; Sri Suharti (Research Center for Biology-Indonesian Institute of Sciences, 2020)
Forage is a feed source for ruminant livestock, but one of the limiting factors of forage is high content of fiber in old forage plants. The fiber content in forage can only be degraded by rumen microbes. One of the rumen microbes that has fiber degrading activity is rumen anaerobic fungi because it can produce very active enzymes to degrade lignocellulose. The rumen anaerobic fungi are divided into several genera which are grouped base on the number of flagella in zoospores, thallus morphology and rhizoid type. The presence of fungi in the rumen is very important because fungi can form rhizoid which will penetrate the feed particles and degrade plant cell walls physically and chemically. In addition, fungi can produce fiber degrading enzymes such as cellulase, hemicellulase, pectinase, and lignocellulase which can increase feed digestibility. However, in Indonesia there is not much study of the potential for rumen anaerobic fungi, so the aims of this review paper is to discuss the potential of anaerobic fungi rumen in improving fiber digestibility in livestock.